Relative Income and Life Satisfaction of Turkish Immigrants: The Impact of a Collectivistic Culture - Devrim Dumludag; Ozge Gokdemir; Maarten C.M. Vendrik (Institute for the Study of Labor (IZA), 2015)
This study examines the effects of social comparison with a wide range of reference groups on the life satisfaction of Turkish immigrants in the Netherlands. For two sets of ethnic and life-domain reference groups, results are obtained that deviate from the findings of recent studies and that suggest the impact of the collectivistic subculture of the Turkish immigrants. Perceived importance of income comparison with Dutch natives is positively correlated to life satisfaction, supporting an interpretation of this comparison as a positive emancipatory stimulus in the pursuit of self-improvement of the Turkish immigrants. Perceived importance of income comparison with relatives in the Netherlands is positively correlated to life satisfaction as well, which can be interpreted in terms of an underlying feeling of connectedness with one's relatives. On the other hand, Turkish immigrants who have a higher household income than relatives are significantly less satisfied with their life, suggesting the unattractiveness of deviating too much from one's relatives. For other reference groups some interesting results are obtained as well.
Keywords: I31; Z13; J15; 330; happiness; life satisfaction; relative income; social comparison; collectivistic; immigrants